Analisis Pembatalan Perkawinan dalam Perspektif Undang-Undang Nomor 1 Tahun 1974 - Keysha Rafa Dayinta; Renny Supriyatni; Sridewi Anggraeni Wiyono (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The issue of marriage annulment in Indonesian law reveals a tension between formal legal norms and dynamic judicial practices, particularly in the application of Law No. 1 of 1974 and its amendments. This study aims to analyze the normative construction, judicial implementation, and legal implications of marriage annulment within the Indonesian legal system. The method employed is normative legal research using legislative, conceptual, and case-based approaches, through analysis of laws, implementing regulations, and relevant court decisions. The results of the study indicate that the annulment of marriage functions as a corrective mechanism against legal defects from the outset; however, in practice, there are variations in judicial interpretation influenced by teleological approaches and sociological considerations. The discussion confirms that while there is consistency in certain cases such as identity fraud, unauthorized polygamy, and violations of age limits, inconsistencies still arise due to the absence of uniform interpretive guidelines. The legal implications of annulment encompass the status of children, joint property, and civil registration, thus requiring the strengthening of regulations and legal harmonization to ensure legal certainty and justice.